Investigation of spectroscopic properties of Sm3+-doped oxyfluorophosphate glasses for laser and display applications. (February 2019) - Neelima, G.; Kummara, Venkata Krishnaiah; Ravi, N.; Suresh, K.; Rasool, Sk. Nayab; Tyagarajan, K.; Prasad, T. Jayachandra
Graphical abstract: Fig. Emission spectra of Sm 3+ -doped oxyfluorophosphate glasses as a function of Sm 3+ ions concentration under 401 nm excitation. Highlights: Samarium (Sm 3+ )-doped oxyfluoro-titania-phosphate (PCfBfTiS) glasses have been fabricated by melt-quenching technique. Judd-Ofelt (JO) phenomenological intensity parameters (Ω2, Ω4, Ω6 ) have been estimated by means of the absorption spectrum. Radiative properties have been obtained by utilizing the JO parameters and refractive index. Lifetime of the 4 G5/2 level of Sm 3+ ions has been evaluated by analysing the decay curves. Abstract: In this manuscript, samarium (Sm 3+ )-doped titania-oxyfluorophosphate (PCfBfTiS) glasses have been fabricated using regular melt-quenching procedure. These glass samples were investigated through optical absorption, photoluminescence excitation, emission and decay characterization techniques. An intense emission was professed at the wavelength of 598 nm owing to the 4 G5/2 → 6 H7/2 transition of Sm 3+ ions under 401 nm excitation. In addition, the reddish-orange emission was also perceived at around 645 nm. Stimulated emission cross-section of 2.0 mol% Sm 3+ -doped PCfBfTiS20 glass was found to be 0.47 × 10 −22 cm 2, which was described to be efficient among other reported glasses. Photoluminescence (PL) decay profiles were demonstrated that the lifetime was increased up to 0.5 mol% Sm 3+ -doped PCfBfTiS05 glass then it was decreased for high Sm 3+ ions concentration. Moreover, CIE color coordinates proven that the emission of Sm 3+ ions was appeared in the reddish - orange region.